2022
DOI: 10.1177/0032258x221102271
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the lie: A smallest space analysis of truthful and deceptive mock-informant accounts

Abstract: Detecting informant deception is a key concern for law enforcement officers, with implications for resource-management, operational decision-making and protecting officers from risk of harm. However, the situational dilemma of a police informant, otherwise known as a Covert Human Intelligence Source (CHIS), is unique. Informants are tasked to obtain information about the transgressive actions or intentions of their associates, knowing they will later disclose this information to a handler. Thus, techniques for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is also worth remembering that the RWITS-US model was designed for use on established cooperative informants as this appears to be the dominant situation in practice (Kleinman, 2006;Nunan, et al, 2020a;Nunan, et al, 2020b), however, the process involved in recruiting informants and establishing that cooperative relationship is underresearched (Dabney & Tewksbury, 2016) and a greater understanding of this process could inform the implementation of the RWITS-US (or any other) interview model. Moffett et al (2021) found an overriding concern with detecting deception amongst informant handlers, and whilst deception was not manipulated in the current study, previous research has found that narrative analysis of a mock-informant account can assist in the identification of deceit (Moffett et al, 2022). Given that the RWITS-US model is specifically designed to elicit a gossip narrative, the detection of deceit may also benefit from its use, and this would provide another opportunity for future research.…”
Section: Implications For Practice and Future Directionsmentioning
confidence: 72%
See 3 more Smart Citations
“…It is also worth remembering that the RWITS-US model was designed for use on established cooperative informants as this appears to be the dominant situation in practice (Kleinman, 2006;Nunan, et al, 2020a;Nunan, et al, 2020b), however, the process involved in recruiting informants and establishing that cooperative relationship is underresearched (Dabney & Tewksbury, 2016) and a greater understanding of this process could inform the implementation of the RWITS-US (or any other) interview model. Moffett et al (2021) found an overriding concern with detecting deception amongst informant handlers, and whilst deception was not manipulated in the current study, previous research has found that narrative analysis of a mock-informant account can assist in the identification of deceit (Moffett et al, 2022). Given that the RWITS-US model is specifically designed to elicit a gossip narrative, the detection of deceit may also benefit from its use, and this would provide another opportunity for future research.…”
Section: Implications For Practice and Future Directionsmentioning
confidence: 72%
“…Whilst the cognitive approach may not be suitable with informants, Moffett et al (2022) were able to manipulate deception within a simulated informant paradigm (incorporating the three stages of tasking, social interaction and de-brief) and found that the way in which informants presented their narrative role differed between truthful and deceptive participants, with deceptive content frequently co-occuring alongside content consistent with low-potency narrative roles. Although deception was not manipulated within the current study, the method adopted by Moffett et al provides handlers with a non-interventionary approach to detecting informant deception based on narrative analysis, and can therefore be employed following the elicitation of a normal narrative account.…”
Section: Detecting Deceptionmentioning
confidence: 99%
See 2 more Smart Citations